Integrated fecal microbiota and metabolomics analysis of the orlistat intervention effect on polycystic ovary syndrome rats induced by letrozole combined with a high-fat diet - Jianmei Yang; Enli Wang; Mingmin Jiang; Yujun Tan; Fangfang Yao; Chenghong Sun; Lihong Pan; Ling Gao; Jingchun Yao (BMC, 2023)
Abstract Background This study aimed to compare the characteristics of the gut microbiota and their metabolite profiles between polycystic ovary syndrome (PCOS) and orlistat-treated PCOS rats (ORL-PCOS), which could help to better understand the underlying mechanism of the effect of orlistat on PCOS. Methods PCOS rat models were established using letrozole combined with a high-fat diet. Ten rats were randomly selected as a PCOS control group (PCOS). The other three groups (n = 10/group) were additionally supplemented with different doses of orlistat (low, medium, high). Then, fecal samples of the PCOS and ORL-PCOS groups were analysed by 16S rRNA gene sequencing and untargeted metabolomics. Blood samples were collected to detect serum sex hormones and lipids. Results The results showed that orlistat attenuated the body weight gain, decreased the levels of T, LH, the LH/FSH ratio, TC, TG and LDL-C; increased the level of E2; and improved estrous cycle disorder in PCOS rats. The bacterial richness and diversity of the gut microbiota in the ORL-PCOS group were higher than those in the PCOS group. The ratio of Firmicutes to Bacteroidetes was decreased with orlistat treatment. Moreover, orlistat treatment led to a significant decrease in the relative abundance of Ruminococcaceae and Lactobacillaceae, and increases in the abundances of Muribaculaceae and Bacteroidaceae. Metabolic analysis identified 216 differential fecal metabolites in total and 6 enriched KEGG pathways between the two groups, including steroid hormone biosynthesis, neuroactive ligand-receptor interaction and vitamin digestion and absorption. Steroid hormone biosynthesis was the pathway with the most significant enrichment. The correlations between the gut microbiota and differential metabolites were calculated, which may provide a basis for understanding the composition and function of microbial communities. Conclusions Our data suggested that orlistat exerts a PCOS treatment effect, which may be mediated by modifying the structure and composition of the gut microbiota, as well as the metabolite profiles of PCOS rats.